مدى مشروعية تقييد حريات الأفراد خلال الأزمات الصحية: نموذج جائحة كورونا "Covid-19" - مخلوف، لبنى محمد علي (جامعة مدينة السادات - كلية الحقوق, 2020)
ان التمتع الكامل بالحق في الصحة باعتباره حق أساسي من الحقوق والحريات العامة لئن كان يقتضي تقييد بعض حقوق الانسان في إطار مبدأ حماية الأمن والنظام العامين فان حماية تلك الحقوق والحريات ترتبط دستوريا بدولة القانون. وتأسيسا على ذلك فان أي حديث عن حماية حقوق الانسان أو تقييدها يبدو في سياقه العام مرتبطا بضرورة المواءمة بين التشريعات الوطنية ونطاق تطبيق المعايير الدولية لحقوق الانسان. وإذا كانت حماية الصحة العامة باعتبارها مكونا من مكونات النظام العام التقليدي تسمح بتقييد حقوق الانسان فانه في ظل الوضعية الراهنة المتعلقة بالأزمة الصحية المرتبطة بوباء كورونا (covid-19). وما تفرضه من التدابير الاحترازية للوقاية من هذا الوباء العالمي يمكن اعتباره حالة صحية تمثل بطبيعتها أو بخطورتها طابع الكارثة العمومية ولعل ذلك ما اقتضي تمديد اعلان حالة الطوارئ في البلاد بجانب اتخاذ التدابير والاجراءات الاحترازية مثل فرض حظر التجول واغلاق الحدود وفرض بعض الاجراءات الصحية كالحجر الصحي تأسيسا على ذلك يدور موضوع بحثنا عن امكانية أن تضمن السياسة الوطنية في مجال حقوق الانسان تمتع الانسان بحقوقه وحرياته العامة في ظل التدابير الاحترازية والمتخذة كوسيلة لتعزيز النظم الصحية بشكل عام في ظل جائحة "فيروس كورونا "انطلاقا من ضرورة التزام الدولة باحترام الاتفاقيات الدولية لحقوق الأنسان.
The full enjoyment of the right to public health as a basic right and public freedoms, while it requires restricting some human rights within the framework of the principle of protecting public security and order The protection of these rights and freedoms is constitutionally linked to the rule of law Based on this, any talk about protecting or restricting human rights appears in its general context linked to the need for harmonization between national legislation and the scope of application of international human rights standards. If the protection of public health as a component of the traditional public order permits the restriction of human rights, then it is in the current situation related to the health crisis associated with the Corona epidemic (covid-19) The precautionary measures it imposes to prevent this global epidemic can be considered a health condition that, by its nature or gravity, represents the nature of a public disaster, and perhaps this required the extension of the declaration of a state of emergency in the country besides taking precautionary measures and measures such as imposing curfews, closing borders and imposing some Based on this, the topic of our research on how a national policy in the field of human rights can guarantee the enjoyment of human rights and public freedoms in light of precautionary measures taken as a means to strengthen health systems in general in light of the "Corona- virus" pandemic based on the need for the state to respect international human rights conventions health measures such as quarantine.
Keywords: الأزمات الصحية -- جائحة كورونا -- حقوق الإنسان -- النظام العام -- القوانين والتشريعات